The future of public transport in light of solutions for sustainable transport development - Kazimierz LEJDA; Maksymilian MĄDZIEL; Sylwia SIEDLECKA; Edyta ZIELIŃSKA (Scientific Journal of Silesian University of Technology. Series Transport, 2017)
The paper highlights possible directions in the development of sustainable public transport solutions. When appropriately identified and implemented, such solutions can contribute to improved quality of urban life by reducing the adverse effects of transport on human health and the natural environment. The paper also raises questions about implementing pedestrian traffic zones, expanding the level of cycling, and introducing a workable parking policy, congestion charges, electromobility and intelligent systems for road traffic management in conurbations.